Comparison of Railway Regulations Between Indonesia and Japan from a Consumer Protection Perspective: What and How? - Churniawan, Erifendi; Ependi, Ahmad (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the comparative regulatory framework governing the railway systems in Indonesia and Japan from the perspective of consumer protection. The research is grounded in the significance of ensuring quality public services in the railway transportation sector and the necessity of safeguarding consumer rights as service users. The primary objective of this research is to analyze the differences and similarities in railway regulations between Indonesia and Japan and to evaluate the extent to which consumer protection is accommodated within policy and implementation frameworks. This study employs a normative legal research method, utilizing a comparative law approach and a conceptual approach. Data analysis techniques include document review, statutory and regulatory analysis, and literature study related to transport regulation and public policy. The novelty of this study lies in its specific focus on consumer protection within railway transport regulation—an aspect that has rarely been studied comparatively between two countries with differing legal systems and infrastructure frameworks. The findings indicate that Japan has developed a more integrated consumer protection system, emphasizing service standards, compensation mechanisms, and operator accountability. In contrast, consumer protection in Indonesia remains general in nature and has yet to be regulated specifically within the railway sector. The study recommends that Indonesian policymakers strengthen railway regulations by explicitly incorporating principles of consumer protection and adopting best legal practices from Japan’s more consumer-oriented regulatory system.